Experiences of Fertiliser-treatment in Eucalypts - a Discussion - Bardhan Roy, B. K. (Indian Forester, 1976)
Information backed by statistical analysis on the growth responses of Eucalypts to different fertiliser-treatment is very meagre. Intriguing growth responses either with N or P alone or with the combination of the two tend to suggest that the crops most likely to benefit from fertilising are those growing on soils which have moderately good physical characteristics, but a relatively low level or chemical fertility. Besides, tendency of Phosphatic compound to remain in a threshold stage probably explains why addition of P-compound fails to show any response to growth. Optimum level of investment in fertilising is often difficult to judge. Continued research in the line would provide data to strike the level of profitable fertilisation, the time of application, the type of fertilser for the best development of the crop and the minimal requirement of the fertiliser.